Rekonstruksi Pengembalian Kerugian Keuangan Negara Sebagai Alternatif Pengganti Pidana Penjara - Sudarmanto, Kukuh; Cyzentio Chairilian, Muhammad Alvin; Sukarna, Kadi (JURNAL USM LAW REVIEW, 2023)
The purpose of this study is to examine the system of recovering state financial losses in the criminal justice system for corruption in Indonesia and the reconstruction of state financial losses as an alternative to imprisonment. This research is included in non-doctrinal research, using normative-empirical research methods. The results of the research describe, the recovery of state financial losses carried out by the Prosecutor's Office through asset tracing and the implementation of Judge's decisions, does not indicate the existence of an optimal law enforcement system for efforts to save state assets. Only an average of 12.3%. It is necessary to reconstruct the recovery of state financial losses by reconstructing Article 4 Jo Article 18 Paragraph (1) letter b of Law no. 20 of 2001 concerning the Second Amendment to Law Number 31 of 1991 and the reconstruction of Article 5 paragraph (1) letter b Regulation of the Attorney General of the Republic of Indonesia No. 15 of 2020, namely the return of state finances can be realized in the settlement of cases through a restorative justice approach at the High Court as an alternative to imprisonment. Tujuan penelitian ini ialah untuk mengkaji mengenai sistem pengembalian kerugian keuangan negara dalam sistem pemidanaan tindak pidana korupsi di Indonesia dan rekonstruksi pengembalian kerugian keuangan negara sebagai alternatif pengganti pidana penjara. Penelitian ini masuk dalam penelitian non-doktrinal, dengan menggunakan metode penelitian normatif-empiris, Hasil penelitian menjabarkan, pengembalian kerugian keuangan negara yang dilaksanakan oleh Kejaksaan melalui aset tracing dan pelaksanaan putusan Hakim, tidak menunjukan adanya suatu sistem penegakan hukum yang optimal terhadap upaya penyelamatan kekayaan negara. Hanya rata-rata sebesar 12,3%. Perlu adanya rekonstruksi pengembalian kerugian keuangan negara dengan melakukan rekonstruksi Pasal 4 Jo Pasal 18 Ayat (1) huruf b UU No. 20 tahun 2001 tentang Perubahan Kedua Undang-Undang Nomor 31 Tahun 1991 dan rekonstruksi Pasal 5 ayat (1) huruf b Peraturan Jaksa Agung RI No. 15 Tahun 2020, yakni pengembalian keuangan negara dapat diwujudkan dalam penyelesaian perkara melalui pendekatan restorative justice di Kejaksaan Tinggi sebagai alternatif pengganti pidana penjara.